Clozapine augmentation with cariprazine for negative symptoms: a case series and literature review - Ebenezer Oloyede; Ivana Clark; Shubhra Mace; Eromona Whiskey; David Taylor (SAGE Publishing, 2022)
Only about 50% of patients with treatment-resistant schizophrenia respond to clozapine, and many more patients continue to experience ongoing and prominent negative symptoms. These negative symptoms, for which there are limited pharmacological options, may represent the greatest barrier to functional recovery. Cariprazine is a novel antipsychotic drug that is a partial agonist at dopamine D 2 and D 3 receptors with preferential binding to the D 3 receptor, antagonism of 5HT 2B receptors, and partial agonism at 5HT 1A receptors. Cariprazine is currently licenced for the treatment of schizophrenia in Europe and the United States and has also been approved for bipolar disorder in the United States. There is a limited body of evidence to suggest clinical effectiveness as an augmentation strategy for negative symptoms in those treated with clozapine. In this case series, we present five cases of successful treatment of negative symptoms by clozapine combined with cariprazine in treatment-resistant psychosis.